1989
DOI: 10.1084/jem.169.5.1543
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide. A macrophage product responsible for cytostasis and respiratory inhibition in tumor target cells.

Abstract: Once activated by agents such as IFN-y and bacterial LPS, macrophages (MO)t can inhibit the growth of a wide variety of tumor and microbial targets (1, 2) . Although MO products such as hydrogen peroxide, TNFa, and IL-1 cause cytostasis and/or cytotoxicity (3-5), in many cases these mediators do not appear to be involved . With some targets, Mo-mediated cytostasis and injury to the mitochondria) electron transport chain (METC) require a process associated with MO oxidation of the guanido nitrogens of L-arginin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
775
0
6

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,623 publications
(798 citation statements)
references
References 49 publications
17
775
0
6
Order By: Relevance
“…ociated with the From our results, the functional significance of NO production in at AM might be lung cancer is not clear. Activated macrophages produce high igh some of our levels of NO that destroy or prevent the division of tumour cells by :ers, our results inhibition of DNA replication and prevention of mitochondrial in the level of respiration (Stuehr et al, 1989;Moncada et al, 1991). NO was or in nitrite prodemonstrated to account for the macrophage cytotoxic activities suggesting that against tumour cells, and to be related to tumour regression (Stuehr bute, to a trivial et al, 1989;Nathan et al, 1991;Radomski et al, 1991).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…ociated with the From our results, the functional significance of NO production in at AM might be lung cancer is not clear. Activated macrophages produce high igh some of our levels of NO that destroy or prevent the division of tumour cells by :ers, our results inhibition of DNA replication and prevention of mitochondrial in the level of respiration (Stuehr et al, 1989;Moncada et al, 1991). NO was or in nitrite prodemonstrated to account for the macrophage cytotoxic activities suggesting that against tumour cells, and to be related to tumour regression (Stuehr bute, to a trivial et al, 1989;Nathan et al, 1991;Radomski et al, 1991).…”
Section: Discussionmentioning
confidence: 67%
“…The oncolytic activity of macrophages is either mediated by direct macrophage-to-tumour cell contact (Bucana et al, 1983) or attributed to the production of soluble tumour cytotoxic factors, such as tumour necrosis factor-a (TNFoc), interleukin I (IL-1), IL-6, cytolytic proteases, arginases, lysosomal enzymes, prostaglandins, oxygen radicals and reactive nitrogen species, particularly NO (Carswell et al, 1975;Currie, 1978;Adams et al, 1980;Hibbs et al, 1988;Nathan, 1991 is dependent on the synthesis of NO (Hibbs et al, 1988). The production of NO from activated macrophages destroys or prevents tumour cell division by inhibition of DNA replication and restraint of mitochondrial respiration (Stuehr et al, 1989;Moncada et al, 1991). Furthermore, the constitutive and inducible NOS is also present in several types of tumour cells, including colorectal adenocarcinoma (Radomski et al, 1991), gynecological carcinoma (Thomsen et al, 1994, neuroblastoma (Forstermann et al, 1990) and dermal squamous cell carcinoma (Villiotou et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have also shown that this bactericidal activity correlates with the depletion of intracellular iron in this cell line. Nitric oxide radicals generated by IFN--activated macrophages react with iron-sulphur prosthetic groups of the enzymes necessary for cellular functions such as (i) mitochondrial respiration, which may limit the ability of host cells to produce ATP [10,11]; (ii) DNA replication requiring ribonucleotide reductase [36]; and (iii) the citric acid cycle [12,37], and these radicals are released # 1996 Blackwell Science Ltd, Clinical and Experimental Immunology, 104:48-53 Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in nitrogenous waste may also reflect host-defensive measures. [121][122][123][124] During acute infections, proinflammatory cytokines and interferon-gamma stimulate the production of nitric oxide 123 as do bacterial lipopolysaccharides 125 . Nitric oxide acts as a highly potent microbicidal and tumoricidal agent, 121 and has immunomodulatory functions.…”
Section: Blood Urea Nitrogen and Creatininementioning
confidence: 99%